(3GdChQGb GdJLGQjI hGdEadGSs - (3Ydj(B, (3GdHGQhOjs ((3GdEScfOQjI(B:s (3OGQ GdeWHhYGJ GdLGeYjI(B,s, 2000)
(3GdChQGb GdJLGQjI(B- (3GdceHjGdI(B- (3JOGhd GdceHjGdI(B- (3VeGfGJ GdhaGA HGdceHjGdI(B- (3GdSbhW hGdJbGOe(B- (3CKQ GdJYGed HGdceHjGdI aj GdOjf GdGUdj(B- (3GdEadGS(B- (3TgQ GdEadGS(B- (3GdBKGQ GdeJQJHI Ydi Mce GdEadGS(B- (3eUjQ GdJadjSIs
Keywords: (3GdChQGb GdeGdjIs; (3GdJLGQIs; (3GdbGfhfs